A fishing expedition to discover the pollinators of several subtropical Apocynaceae. (13th February 2020) - Koptur, Suzanne; Barrios, Beyte; Valdes, Imeña; Nusrat, Maha
Abstract : Premise: Flowers of the Apocynaceae (milkweed family) have complex structures and pollination mechanisms. Pollen removal and deposition in Angadenia, Pentalinon, and Echites are similar, with anthers releasing pollen onto the sterile style head. The mid‐style head excretes a glue that coats the mouthparts of vistors to aid in the transfer of pollen. Subsequent probes may deposit pollen on the receptive stigmatic surface on the lowest part of the style head, with fertilization resulting after pollination by compatible pollen. Methods: By employing fishing line of different diameters, which reflected the diameters of the mouthparts of the different insect visitors, we determined the widths best able to remove and deposit pollen, thereby revealing which of the visitors could be effective pollinators, and which may be only nectar robbers. Results: We previously found that mouthpart (proboscis) width is correlated with pollen transfer effectiveness in Angadenia berteroi and confirmed this here in two other species, Pentalinon luteum and Echites umbellatus . Our data allowed the prediction of the most effective pollinators of these two other species. Discussion: The simulation of flower visitor mouthparts using fishing line can provide useful data for evaluating the potential for effective pollen removal and deposition by different visitors.